EFFECT OF ODOR EMISSIONS FROM PIG LIVESTOCK ON THE HEALTH OF RURAL RESIDENTS OF CONCÓRDIA, SANTA CATARINA, BRAZIL (Revista de Ciências Agroveterinárias, 2004)
The present study is part of a multidisciplinary research project on the effects of odor emissions from swine facilities in the state of Santa Catarina, Brazil. The city of Concórdia was chosen as the study site because it is one of the major Brazilian swine-producing counties. A questionnaire was applied to 102 rural residents in order to determine the source of odors, nuisance level, and health symptoms caused by this type of environmental pollution. The results showed that the major sources of odor emissions were related to the application of untreated manure on the soil and inadequate storage facilities. The nuisance level reached 72.3%, and odors ranged from offensive to very offensive. Changes in behavior and health symptoms, characterized by restlessness, irritability, malaise, nausea, headache, stomachache, loss of appetite, sleep disorders, and breathing disorders, and the necessity to close the windows to keep off odor nuisance, were caused by odor emissions from swine facilities. The questionnaire proved to be a useful tool in evaluating the environmental impact and monitoring the emission sources of air pollutants.
Keywords: Odor perception; health symptoms; rural residents; odor nuisance; pig farming.